PENGARUH SERAT BUAH PINANG TERHADAP KUAT TEKAN BETON - Hermawati, Hermawati; Herawati, Herawati (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2023)
Concrete material innovations are no emerging more and more and are something that is really needed, one of which is material innovation with the addition of fiber. Fiber concrete is a mixture of concrete plus fiber. The fiber material can be asbestos fiber, plastic fiber (poly-propyline), or pieces of steel wire, plant fibers (hemp, coconut fiber, bamboo, palm fiber). The purpose of adding fiber is to improve or increase the mechanical properties of concrete in the form of tensile strength, compressive strength and flexural strength. This research uses areca nut skin fiber, the skin and seeds are separated, then the betel nut fiber is spread apart so that it does not clump when mixing, then the betel nut fiber is mixed little by little into the concrete mixture. This research aims to determine the effect of adding Areca nut fiber on the compressive strength of concrete aged 7, 14 and 28 days. The percentage of areca nut shell fiber used in this research as 1.6%, 2.4% and 4%. The research used test objects in the form of cubes measuring 15 x 15 x15 cm, with a sample of 12 pieces of concrete, including 9 pieces of concrete with a mixture of betel nut fiber according to each type of concrete aged 7, 14 and 28 days, and 3 pieces of concrete without mixed/normal. The test carried out on the concrete mixture is the compressive strength of the concrete. From the research results obtained, the results of testing the compressive strength of fiber concrete with a percentage of Areca fruit fiber of 1.6% at concrete ages of 7, 14, and 28 days obtained an average compressive strength result of 7.65 MPa, for testing the compressive strength of concrete with a percentage 2.4% for concrete ages of 7, 14 and 28 days experienced a decrease in average compressive strength of 5.88 MPa and for concrete compressive strength testing with a percentage of 4% for concrete ages of 7, 14 and 28 days there as an increase in average concrete compressive strength. The average is 11.43 MPa.